2011
DOI: 10.1073/pnas.1106896108
|View full text |Cite
|
Sign up to set email alerts
|

Sidestream tobacco smoke is a male germ cell mutagen

Abstract: Active cigarette smoking increases oxidative damage, DNA adducts, DNA strand breaks, chromosomal aberrations, and heritable mutations in sperm. However, little is known regarding the effects of second-hand smoke on the male germ line. We show here that short-term exposure to mainstream tobacco smoke or sidestream tobacco smoke (STS), the main component of secondhand smoke, induces mutations at an expanded simple tandem repeat locus (Ms6-hm) in mouse sperm. We further show that the response to STS is not linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 43 publications
4
49
0
Order By: Relevance
“…We found that the changes in MRSA induced by cigarette smoke exposure persisted even after the stress was removed, suggesting that cigarette smoke exposure induces heritable changes in MRSA. It has been shown that cigarette smoke and secondhand smoke exposures cause heritable changes in mice and rats (45)(46)(47)(48). The data in humans are less vigorous, but one study demonstrated higher rates of asthma in children and grandchildren of women who smoked during pregnancy (49).…”
Section: Discussionmentioning
confidence: 98%
“…We found that the changes in MRSA induced by cigarette smoke exposure persisted even after the stress was removed, suggesting that cigarette smoke exposure induces heritable changes in MRSA. It has been shown that cigarette smoke and secondhand smoke exposures cause heritable changes in mice and rats (45)(46)(47)(48). The data in humans are less vigorous, but one study demonstrated higher rates of asthma in children and grandchildren of women who smoked during pregnancy (49).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, side-stream cigarette smoke is a germ-cell mutagen in rodents but is negative for cytogenetic damage in mouse bone marrow [Marchetti et al, 2011], indicating that an agent can be negative for cytogenetic damage in somatic cells in vivo but still be a germ-cell mutagen. The mutagenicity of smoking, especially the genotoxic effects of smoking on egg and sperm in humans, makes smoking a likely human germ-cell mutagen [DeMarini, 2004].…”
Section: Possible Human Germ-cell Mutagensmentioning
confidence: 99%
“…DOI 10.1002/em Table I. b There are two studies, both in mice [Yauk et al, 2007;Marchetti et al, 2011]. These agents induce similar biomarker effects in humans as they do in animals, such as DNA damage in sperm, as reviewed for ionizing radiation and chemotherapy [Kamiguchi and Tateno, 2002], smoking [DeMarini, 2004], and air pollution [Somers, 2011].…”
Section: Need For a Declaration Panel And Implications Of Declaring Amentioning
confidence: 99%
See 1 more Smart Citation
“…Such sensitivity of ESTR loci signified a potential useful tool for studies of environmental pollution thus, lastly but of equal importance, is their implementation in the analysis of (d) environmental mutagens, including ambient urban/industrial air pollution (Somers et al, 2002(Somers et al, , 2004Yauk et al, 2008;Zhou et al, 2009), diesel exhaust particles (Ritz et al, 2011) and sidestream tobacco smoke (Yauk et al, 2007;Marchetti et al, 2011). A similar detection of de novo mutations in ESTRs has also been observed in vitro, signifying a correlation between the mutation responses of cultured embryonic fibroblasts and germ cells and somatic cells in vivo following treatment with chemical mutagens (Polyzos et al, 2006a(Polyzos et al, , 2006b).…”
Section: Estr Mutation Detection Studiesmentioning
confidence: 99%